2020
DOI: 10.1111/eci.13331
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition in metabolic‐dysfunction‐associated fatty liver disease and cardiovascular outcomes—Systematic review

Abstract: Background: Despite the demonstrated increased cardiovascular (CV) risk associated with metabolic-dysfunction-associated fatty liver disease (MAFLD), genetic variants predisposing to MAFLD were not constantly associated with CV events. Recently, rs641738C > T near membrane-bound O-acyltransferase domain-containing 7 (MBOAT7) has been studied in MAFLD and CV outcomes. Therefore, we aimed to evaluate the association between rs641738C > T in the presence and severity of hepatic steatosis, fibrosis, biochemical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…The meta-analysis included 2,560 cases and 8,738 controls and found no evidence of an association between this variant and a diagnosis of NAFLD (Table S5). One previous systematic review 43 found positive associations between rs641738C>T in adults of Caucasian, Hispanic, and Black descent, with limited data in children (Table S5).…”
Section: Resultsmentioning
confidence: 98%
“…The meta-analysis included 2,560 cases and 8,738 controls and found no evidence of an association between this variant and a diagnosis of NAFLD (Table S5). One previous systematic review 43 found positive associations between rs641738C>T in adults of Caucasian, Hispanic, and Black descent, with limited data in children (Table S5).…”
Section: Resultsmentioning
confidence: 98%
“…Finally, in 2017, Liu et al tested the association of genotypes from the Human Exome Bead Chip with lipid levels and found that both TM6SF2 rs58542926 and PNPLA3 rs738409 variants were associated with lower lipid levels and a lower risk of CAD, but with an increased risk of steatosis and T2D 37 . Finally, the genetic variant rs641738C > T near MBOAT7 , predisposing to raised hepatic fat, MAFLD and susceptibility to develop NASH, did not associate with CAD risk 64 …”
Section: Risk Factors Contributing To Nafld/mafldmentioning
confidence: 99%
“…In some individuals, this seemingly benign fat accumulation in hepatocytes triggers inflammation leading to nonalcoholic steatohepatitis (NASH), liver fibrosis, cirrhosis, and/or development of hepatocellular carcinoma. e progression from NAFLD to these more severe entities is multifactorial and depends on an individual's genetic factors, environmental factors, and abnormal activation of the innate immune system [1][2][3][4][5]. Abnormal activation of the innate immune system leads to persistent low-grade inflammation which leads to tissue injury and fibrosis and has an important role in carcinogenesis [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%